A nanoporous Ru / RuAl / Cu for lithium-carbon dioxide battery cathodes 2+1 Method for preparing o-heterojunction electrocatalyst pole piece

CN117438600BActive Publication Date: 2026-10-30UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311104322.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2026-10-30
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

然而,钌基纳米电催化剂的制备通常以金属盐作为前驱体,采用溶剂热、溶胶凝胶、化学还原、高温处理等方法制备,其工艺复杂、产率较低、组分和结构不易控制,不适宜在实际生产中应用

Benefits of technology

采用简便的条件制备出高质量的纳米多孔Ru/RuAl/Cu2+1O异质结电催化剂极片,反应可调可控、反应条件温和,不需要价格昂贵的设备,制备工艺重复性好、绿色、安全、高效,适于规模化制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117438600B_ABST
    Figure CN117438600B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano-porous Ru / RuAl / Cu for lithium-carbon dioxide battery anode 2+1 Preparation method of O heterojunction electrocatalyst pole piece, Ru / RuAl / Cu with porous structure is prepared by dealloying technology 2+1 O heterojunction electrocatalyst pole piece. The nano-porous Ru / RuAl / Cu 2+1 O heterojunction electrocatalyst three-dimensional skeleton structure is conducive to the conduction of electron, open pore is conducive to gas diffusion and electrode liquid infiltration, large specific surface area and highly tortuous internal structure provide space for the deposition of discharge product and are conducive to the exposure of active site, thereby improving the performance of lithium-carbon dioxide battery. Ru / RuAl / Cu 2+1 O heterojunction electrocatalyst RuAl intermetallic compound with ordered lattice structure and metal excess type Cu 2+1 O all have unique electronic and geometric structure, have abundant heterogeneous interface, can promote electron reconstruction and redistribution, control the adsorption and activation of reactants, products and intermediate species in CO2 reduction and evolution reaction, and obtain excellent intrinsic catalytic activity. At the same time, the catalyst preparation method has the advantages of green, simple, safe and the like, and is easy to realize large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic materials, specifically to a nanoporous Ru / RuAl / Cu material for the cathode of lithium-carbon dioxide batteries. 2+1 Preparation method of O heterojunction electrocatalyst electrode. Background Technology

[0002] Rechargeable lithium-carbon dioxide batteries use CO2 as the working medium to achieve the interconversion between electrical energy and chemical energy, realizing the resource utilization of CO2, and have a power output of up to 1876 Wh / kg. –1 The theoretical energy density of lithium-carbon dioxide batteries has shown broad application prospects in the field of electrochemical energy conversion and storage. However, the discharge product Li₂CO₃ of lithium-carbon dioxide batteries has high thermodynamic stability, electronic insulation, and electrochemical inertness, requiring a high voltage to drive its electrochemical oxidation and decomposition in lithium-carbon dioxide batteries. This high charging voltage not only results in low energy conversion efficiency but also causes parasitic side reactions such as electrolyte decomposition, leading to poor cycle stability and rate performance of lithium-carbon dioxide batteries. Therefore, developing high-performance CO₂ electroreduction and precipitation catalysts to reduce the energy barrier of Li₂CO₃ decomposition reaction is key to the development of lithium-carbon dioxide batteries.

[0003] Ruthenium is an excellent catalyst for lithium-carbon dioxide batteries, but its low natural abundance and high price hinder its large-scale application. Introducing other metals into ruthenium can significantly alter its electronic and geometric structures, thereby improving its catalytic activity for CO2 electroreduction and evolution reactions, and can also reduce its dosage, thus lowering catalyst costs. Studies have found that Cu with abundant oxygen vacancies... 2+1 Ruthenium (O), with its unique electronic structure, can improve the adsorption and activation of reactants and products in the electroreduction and precipitation of CO2, exhibiting excellent catalytic activity. Combining ruthenium-based materials with Cu... 2+1 Combining ruthenium and oxygen can fully utilize the synergistic advantages of the two catalysts to achieve significant catalytic enhancement. However, the preparation of ruthenium-based nano-electrocatalysts typically uses metal salts as precursors and employs methods such as solvothermal processes, sol-gel processes, chemical reduction, and high-temperature treatment. These processes are complex, have low yields, and their composition and structure are difficult to control, making them unsuitable for practical production applications. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention aims to provide a nanoporous Ru / RuAl / Cu nanoparticle for use as a cathode in lithium-carbon dioxide batteries. 2+1 A method for preparing O heterojunction electrocatalyst electrodes. The preparation process is simple, reproducible, and low-cost, and the resulting nanoporous Ru / RuAl / Cu electrodes are... 2+1O heterojunction electrocatalyst electrodes exhibit excellent performance in lithium-carbon dioxide batteries. Nanoporous Ru / RuAl / Cu electrodes prepared using dealloying technology... 2+1 O heterojunction electrocatalysts possess open and interconnected pores and a large specific surface area, which facilitates the formation of abundant multiphase reaction interfaces and the deposition of discharge products, thereby improving the apparent kinetics of the catalyst; RuAl intermetallic compounds with ordered lattice structures and Cu containing abundant oxygen vacancies. 2+ All 1O have unique electronic and geometric structures, and the nanoporous Ru / RuAl / Cu 2+1 The rich interfaces of O heterojunction electrocatalysts can drive electron migration and redistribution, thereby enhancing the intrinsic activity of the catalyst.

[0005] The present invention involves preparing nanoporous Ru / RuAl / Cu alloys by free etching of a RuCuAl matrix alloy in a dilute acid or dilute alkali aqueous solution. 2+1 O heterojunction electrocatalyst electrode. Nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst consists of intermetallic compounds RuAl phase, Ru phase, and Cu phase with abundant oxygen vacancies. 2+1 Composed of an O-phase, multiple interpenetrating phases form a heterojunction electrocatalyst with abundant nano-heterogeneous interfaces. A nanoporous Ru / RuAl / Cu... 2+1 The O heterojunction electrocatalyst is used as the positive electrode catalyst. Polytetrafluoroethylene (PTFE) is used as the binder, and Ketjen carbon is used as the conductive agent to form the positive electrode sheet. After assembly into a lithium-carbon dioxide battery, the battery operates at 200 mA g. −1 At current density, the battery can stably cycle more than 150 times. When the battery is deeply discharged and then recharged, it can be fully reversibly fully charged, and the charging termination voltage is stable below 4.4 V, demonstrating good long-term cycle stability and reversibility.

[0006] As a preferred technical solution, the nanoporous Ru / RuAl / Cu 2+1 The preparation of O heterojunction electrocatalysts specifically includes the following steps: (1) High-purity ruthenium, copper and aluminum are melted in a vacuum arc furnace or a high-frequency induction furnace to obtain RuCuAl matrix alloy ingots. The atomic percentage of Ru in the RuCuAl matrix alloy ingots is 0.1-50%, the atomic percentage of Cu is 1-50%, and the atomic percentage of Al is 50-95%. (2) The RuCuAl matrix alloy ingot obtained in step (1) is polished with sandpaper to remove the oxide layer on the surface. The molten liquid alloy is rapidly solidified on a copper roller rotating at a high speed of 800 to 5000 r / min through a single roller quenching system to obtain RuCuAl matrix alloy strips with a thickness of 0.1 to 500 micrometers, a width of 0.1 to 5 cm, and a length of 0.1 to 20 cm. (3) The RuCuAl matrix alloy strips obtained in step (2) are immersed in dilute acid or dilute alkali aqueous solution for free corrosion. The corrosion temperature range is 20~50 ℃ and the corrosion time is 1~100 h. The product is washed multiple times with ultrapure water until the washing solution is neutral. Vacuum drying is then performed to obtain multi-nano porous Ru / RuAl / Cu 2+1 O heterojunction electrocatalyst.

[0007] As a preferred technical solution, the prepared nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst is composed of Ru, RuAl, and Cu. 2+1 The structure consists of three phases: O, Ru (5%–30% by weight), RuAl (5%–30% by weight), and Cu. 2+1 The molar percentage of the O phase is 50%~90%, and the nanoporous Ru / RuAl / Cu phase is... 2+1 The pore wall size of the O heterojunction electrocatalyst is 5~500 nm, and the pore size is 5~500 nm.

[0008] As a preferred technical solution, the dilute acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution with a concentration range of 0.01~2 mol / L; the dilute alkali aqueous solution is sodium hydroxide or potassium hydroxide aqueous solution with a concentration range of 0.01-3 mol / L.

[0009] As a preferred technical solution, in nanoporous Ru / RuAl / Cu 2+1 Nanoporous Ru / RuAl / Cu in O heterojunction electrocatalyst electrode 2+1 The mass fraction of the O heterojunction electrocatalyst is 20%–60%, the mass fraction of Ketjen carbon is 20%–60%, and the mass fraction of polytetrafluoroethylene is 5%–30%.

[0010] Advantages of this invention: High-quality nanoporous Ru / RuAl / Cu was prepared using simple conditions. 2+1 O heterojunction electrocatalyst electrodes offer tunable and controllable reactions under mild conditions, do not require expensive equipment, and feature a reproducible, green, safe, and efficient preparation process suitable for large-scale production.

[0011] Nanoporous Ru / RuAl / Cu 2+1The continuous framework structure of O heterojunction electrocatalysts facilitates electron conduction, the open channels facilitate gas diffusion and electrolyte wetting, and the large area and highly tortuous internal structure facilitate the exposure of active sites and provide space for the deposition of discharge products, thereby improving the apparent kinetics of CO2 electroreduction and evolution reactions.

[0012] Nanoporous Ru / RuAl / Cu 2+1 O heterojunction electrocatalysts contain RuAl intermetallic compounds with ordered lattice structures and Cu metals with abundant oxygen vacancies. 2+1 O possesses unique electronic and geometric structures, enabling it to modulate the adsorption and activation of reactants, products, and key intermediates in CO2 electroreduction and precipitation reactions, lowering the energy barrier required for the reaction, and enhancing the intrinsic activity of the catalyst, particularly in nanoporous Ru / RuAl / Cu. 2+1 The O heterojunction electrocatalyst is used as the positive electrode catalyst. After being assembled into a lithium-carbon dioxide battery, it operates at 200 mA g. −1 At current density, the battery can stably cycle more than 150 times. When the battery is deeply discharged and then recharged, it can be fully reversibly fully charged, and the charging termination voltage is stable below 4.4 V, demonstrating good long-term cycle stability and reversibility.

[0013] Nanoporous Ru / RuAl / Cu 2+1 The preparation method used for the O heterojunction electrocatalyst electrode has excellent versatility; the composition and pore size of the heterojunction are adjustable and controllable. Attached Figure Description

[0014] Figure 1 Nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 X-ray diffraction pattern of O heterojunction electrocatalyst; Figure 2 Nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 Scanning electron microscope image of O heterojunction electrocatalyst; Figure 3 Nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 Transmission electron microscope images and elemental distribution images of O heterojunction electrocatalysts; Figure 4 Nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 Energy dispersive spectrum of O heterojunction electrocatalyst; Figure 5 The nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 A lithium-carbon dioxide battery assembled with an O heterojunction electrocatalyst electrode, at 200 mA g -1Evolution curve of charge / discharge termination voltage obtained from DC charge / discharge test at current density; Figure 6 The nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 A lithium-carbon dioxide battery assembled with an O heterojunction electrocatalyst electrode, at 200 mA g -1 Time-voltage curves obtained from DC charge-discharge tests at current density; Figure 7 The nanoporous Ru / RuAl / Cu prepared in Example 1 2+1 A lithium-carbon dioxide battery assembled with an O heterojunction electrocatalyst electrode, at 200 mA g -1 The deep charge-discharge curves obtained from DC charge-discharge tests at current density. Detailed Implementation

[0015] The present invention will be further described below with reference to embodiments. The described embodiments and their results are for illustrative purposes only and should not, and will not, limit the invention as described in detail in the claims. Example 1

[0016] A nanoporous Ru / RuAl / Cu for lithium-carbon dioxide battery cathode 2+1 A method for preparing O heterojunction electrocatalyst electrodes, comprising the following steps: With a mass fraction of 45%, nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst is used as the positive electrode catalyst, with 45% Ketjen carbon as the conductive agent and 10% polytetrafluoroethylene as the binder, to form the positive electrode sheet for assembly into a lithium-carbon dioxide battery.

[0017] The nanoporous Ru / RuAl / Cu 2+1 The preparation of O heterojunction electrocatalysts specifically includes the following steps: (1) High-purity ruthenium, copper and aluminum are smelted in a vacuum arc furnace or a high-frequency induction furnace to obtain Ru3Cu. 12 Al 85 Parent alloy ingot; (2) The Ru3Cu obtained in step (1) 12 Al 85 The base alloy ingot was polished with sandpaper to remove the surface oxide layer. The molten liquid alloy was then rapidly solidified on a copper roller rotating at a high speed of 2000 r / min using a single-roller quenching system, resulting in a Ru3Cu ingot with a thickness of approximately 100 micrometers, a width of approximately 0.3 cm, and a length of approximately 3 cm. 12 Al 85 Parent alloy strip; (3) The Ru3Cu obtained in step (2) 12 Al 85 The parent alloy strip was subjected to free corrosion by immersion in a 0.5 mol / L sodium hydroxide aqueous solution at a corrosion temperature of 25 °C for 48 h. The product was washed multiple times with ultrapure water until the washing solution was neutral, and then vacuum dried to obtain a multi-nano porous Ru / RuAl / Cu alloy. 2+1 O heterojunction electrocatalyst.

[0018] (4) such as Figure 1 The X-ray diffraction pattern shows that the nanoporous Ru / RuAl / Cu 2+1 O heterojunction electrocatalysts are made of Ru (JCPDS #65–7645), RuAl (JCPDS #65–3207), and Cu. 2+1 O (JCPDS #05–0667) is a three-phase structure.

[0019] (5) such as Figure 2 Scanning electron microscope images and Figure 3 The transmission electron microscope images and elemental distribution images show that the nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst has a pore size of approximately 150 nm and a pore wall size of approximately 50 nm, with ruthenium, copper, oxygen, and aluminum elements evenly distributed.

[0020] (6) For example Figure 4 The energy dispersive spectroscopy (EDS) spectrum shows that the nanoporous Ru / RuAl / Cu 2+1 In the O heterojunction electrocatalyst, the atomic percentages of Ru are 14.6%, Cu is 47.2%, Al is 6.9%, and O is 31.3%. Therefore, the molar percentages of the Ru phase are 16.6%, the RuAl phase is 15.1%, and Cu... 2+1 The molar percentage of the O phase is 68.3%.

[0021] (7) For example Figure 5 and Figure 6 The nanoporous Ru / RuAl / Cu 2+1 A lithium-carbon dioxide battery assembled with an O heterojunction electrocatalyst electrode, at 200 mA g -1 The curves of charge / discharge termination voltage evolution and time-voltage curves obtained from DC charge / discharge tests at current density show that the battery can stably cycle for 170 cycles, or 1770 hours, and the charge / discharge electrode polarization is stable at around 1.4V.

[0022] (8) such as Figure 7The nanoporous Ru / RuAl / Cu 2+1 A lithium-carbon dioxide battery assembled with an O heterojunction electrocatalyst electrode, at 200 mA g -1 The deep charge-discharge curves obtained from DC charge-discharge tests at current density show that the battery's deep discharge capacity can reach 12222 mAh g. –1 Furthermore, during charging, the battery can be fully reversibly charged, with a charging termination voltage of only 4.32 V.

[0023] This invention provides a nanoporous Ru / RuAl / Cu nanoparticle for use as a cathode in lithium-carbon dioxide batteries. 2+1 The method for preparing O heterojunction electrocatalyst electrodes involves selectively etching away some aluminum using dealloying technology to obtain nanoporous Ru / RuAl / Cu electrodes with a three-dimensional porous structure. 2+1 O heterojunction electrocatalyst electrode has excellent catalytic performance for CO2 reduction and precipitation reactions in lithium-carbon dioxide batteries, and its preparation process is simple and suitable for large-scale production.

[0024] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nanoporous Ru / RuAl / Cu nanoparticle for lithium-carbon dioxide battery cathode 2+1 The method for preparing O heterojunction electrocatalyst electrode sheets is characterized by: Nanoporous Ru / RuAl / Cu alloys were prepared by free corrosion of RuCuAl matrix alloys in dilute acid or dilute alkaline aqueous solutions. 2+1 O heterojunction electrocatalyst. Nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst consists of intermetallic compounds RuAl phase, Ru phase, and Cu phase with abundant oxygen vacancies. 2+1 Composed of an O phase, multiple interpenetrating phases form a heterojunction electrocatalyst with abundant nano-heterogeneous interfaces, using nanoporous Ru / RuAl / Cu. 2+1 The O heterojunction electrocatalyst is used as the positive electrode catalyst. Polytetrafluoroethylene (PTFE) is used as the binder, and Ketjen carbon is used as the conductive agent to form the positive electrode sheet. After assembly into a lithium-carbon dioxide battery, the positive electrode is tested at 200 mA g. -1 At current density, the battery can stably cycle more than 150 times. When the battery is deeply discharged and then recharged, it can be fully reversibly fully charged, and the charging termination voltage is stable below 4.4 V, demonstrating good long-term cycle stability and reversibility.

2. The nanoporous Ru / RuAl / Cu nanoparticles for lithium-carbon dioxide battery cathodes as described in claim 1 2+1 The method for preparing O heterojunction electrocatalyst electrode sheets is characterized by: The nanoporous Ru / RuAl / Cu 2+1 The preparation of O heterojunction electrocatalysts specifically includes the following steps: (1) High-purity ruthenium, copper and aluminum are melted in a vacuum arc furnace or a high-frequency induction furnace to obtain RuCuAl matrix alloy ingots. The atomic percentage of Ru in the RuCuAl matrix alloy ingots is 0.1-50%, the atomic percentage of Cu is 1-50%, and the atomic percentage of Al is 50-95%. (2) The RuCuAl matrix alloy ingot obtained in step (1) is polished with sandpaper to remove the oxide layer on the surface. The molten liquid alloy is rapidly solidified on a copper roller rotating at a high speed of 800 to 5000 r / min through a single roller quenching system to obtain RuCuAl matrix alloy strips with a thickness of 0.1 to 500 micrometers, a width of 0.1 to 5 cm, and a length of 0.1 to 20 cm. (3) The RuCuAl matrix alloy strips obtained in step (2) are immersed in dilute acid or dilute alkali aqueous solution for free corrosion. The corrosion temperature range is 20-50 °C and the corrosion time is 1-100 h. The product is washed multiple times with ultrapure water until the washing solution is neutral. Vacuum drying is then performed to obtain multi-nano porous Ru / RuAl / Cu 2+1 O heterojunction electrocatalyst.

3. The nanoporous Ru / RuAl / Cu nanoparticles for lithium-carbon dioxide battery cathodes as described in claim 1 2+1 The method for preparing O heterojunction electrocatalyst electrode sheets is characterized by: The prepared nanoporous Ru / RuAl / Cu 2+1 The O heterojunction electrocatalyst is composed of Ru, RuAl, and Cu. 2+1 The structure consists of three phases: O, Ru (5-30% by weight), RuAl (5-30% by weight), and Cu. 2+1 The molar percentage of the O phase is 50-90%, and the nanoporous Ru / RuAl / Cu phase is... 2+1 The pore wall size of the O heterojunction electrocatalyst is 5–500 nm, and the pore size is 5–500 nm.

4. The nanoporous Ru / RuAl / Cu nanoparticles for lithium-carbon dioxide battery cathodes as described in claim 2 2+1 The method for preparing O heterojunction electrocatalyst electrode sheets is characterized by: In step (3), the dilute acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution with a concentration range of 0.01 to 2 mol / L; the dilute alkali aqueous solution is sodium hydroxide or potassium hydroxide aqueous solution with a concentration range of 0.01 to 3 mol / L.

5. The nanoporous Ru / RuAl / Cu nanoparticles for lithium-carbon dioxide battery cathodes as described in claim 1 2+1 The method for preparing O heterojunction electrocatalyst electrode sheets is characterized by: Nanoporous Ru / RuAl / Cu 2+1 In the O heterojunction electrocatalyst electrode, nanoporous Ru / RuAl / Cu 2+1 The mass fraction of the O heterojunction electrocatalyst is 20%–60%, the mass fraction of Ketjen carbon is 20%–60%, and the mass fraction of polytetrafluoroethylene is 5%–30%.

Citation Information

Patent Citations

  • Preparation and application of cationic MOFs derivative catalyst

    CN113471457A

  • Solid-state sodium-carbon dioxide battery

    US20220140406A1